Distinct patterns of auto-reactive antibodies associated with organ-specific immune-related adverse events - Altan, Mehmet; Li, Quan-Zhen; Wang, Qi; Vokes, Natalie I.; Sheshadri, Ajay; Gao, Jianjun; Zhu, Chengsong; Tran, Hai T.; Gandhi, Saumil; Antonoff, Mara B.; Swisher, Stephen; Wang, Jing; et al. (Frontiers in Immunology, 2023)
The roles of preexisting auto-reactive antibodies in immune-related adverse events (irAEs) associated with immune checkpoint inhibitor therapy are not well defined. Here, we analyzed plasma samples longitudinally collected at predefined time points and at the time of irAEs from 58 patients with immunotherapy naïve metastatic non-small cell lung cancer treated on clinical protocol with ipilimumab and nivolumab. We used a proteomic microarray system capable of assaying antibody reactivity for IgG and IgM fractions against 120 antigens for systemically evaluating the correlations between auto-reactive antibodies and certain organ-specific irAEs. We found that distinct patterns of auto-reactive antibodies at baseline were associated with the subsequent development of organ-specific irAEs. Notably, ACHRG IgM was associated with pneumonitis, anti-cytokeratin 19 IgM with dermatitis, and anti-thyroglobulin IgG with hepatitis. These antibodies merit further investigation as potential biomarkers for identifying high-risk populations for irAEs and/or monitoring irAEs during immunotherapy treatment. Trial registration ClinicalTrials.gov identifier: NCT03391869.